Kanlungan o kulungan a visual, sensorial, and metaphorical materialization of domestic space in the time of a pandemic - Tan Gana, Vanessa J.; Imao, Abdulmari de Leon Jr.; Sta. Ana, Mary Catherine P. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2022)
This thesis project addresses the discourse on how geometric abstraction can be applied to the problem of analyzing, interpreting, and representing human movement patterns in a specific space. One of the repercussions of the ongoing Covid-19 pandemic is the enforced home quarantine to prevent the spread of the disease. Families are obligated to stay cooped together within the restrictive space of their home for long periods of time. This places them in a position where physical as well as psycho-social constraint is experienced by each member of the household. The inquiry focuses on how the inhabitants navigated the reality of confinement while continuing to do their daily activities. Its implication in terms of portraying these temporal occurrences as main criteria in depicting an artwork is expounded critically. The application of geometric forms as the fundamental operational device in configuring human motions and sensations into a structured (and tangible) formation is the guiding principle behind the proposed discourse and resulted artwork.
Thesis (Bachelor of Fine Arts in Painting)--University of the Philippines Diliman
Bibliography: leaf 27
Keywords: Domestic space; Geometric abstraction; Covid-19 pandemic; Marginalized dwelling